Screen tourism in Croatia – Case Study „Game of Thrones“ - Vukašina, Martina; Brechelmacher, Mirela; Miočić, Josip (Oeconomica Jadertina, 2021)
Screen tourism has associated the development of film, and in the Republic of Croatia it has become an increasingly popular form of tourism thanks to the filming of the series "Game of Thrones" in Dubrovnik, around Split and the surroundings of Sibenik. Filming of the popular series has raised a number of new tourism offerings at filming locations, in a way that numerous national and international agencies offer a variety of different trips and excursions comprising visiting the filming locations of the series. Tourism relieing only on natural beauties, which Croatia hasn’t been lacking, is not a model that, in the long run, will contribute to increasing the competitiveness of Croatian tourism compared to other Mediterranean countries. However, investing in the development of the film industry potentially encourages the development of film tourism, which may be an opportunity to reduce the natural beauties and weather dependence of Croatian tourism. The purpose of the research paper is to measure the economic effects of film tourism on the example of the series "Game of Thrones" in the Republic of Croatia. The primary aim of the research is to analyze the characteristics of film tourism on the example of tourism caused by the filming of the series "Game of Thrones". The research paper results should contribute to the creation of a foundation for the development of the audiovisual industry in Croatia, and thus for the development of film tourism.